Testing the Types and Concentrations of Growth Regulators on the Growth of Patchouli Cuttings (Pogostemon cablin Benth.) - Setyoreni Agustin (Contributions of Central Research Institute for Agriculture, 2021)
This study aims to determine the effect of concentrations of Rooton F, young coconut water, and cow urine on the growth of cuttings patchouli stem. Patchouli plant (Pogostemon cablin Benth.) is one of the important essential oil producing plants. The export volume of essential oils has always increased, in 2001 it reached 5,080 tons. Indonesia is the main supplier of patchouli oil in the world, which is almost 90% of the world's needs (Emmyzar, 2004). However, in recent years, patchouli oil exports have shown a downward trend. The cause of the decline was the limited ability to produce patchouli oil. Therefore efforts to increase the production of patchouli oil by way of development patchouli plants wide open. One of these efforts can be done by producing patchouli plants that have good quality. Patchouli plant propagation can be done by cuttings. The success of cuttings can be seen from their roots. Good rooting will produce quality plants fine too. Auxin is a type of plant hormone that can stimulate root growth. Rooton F is an example of a synthetic ZPT ingredient, while young coconut water and cow urine are natural ZPT ingredients. The three materials have their advantages and disadvantages. With the difference in the content of the three ingredients, it will also have a different effect on the growth of patchouli cuttings. In observing the number of leaves aged 6 wap, 75% rooton-F gave a yield of 4.67 leaves and was not different from the treatment of 75% coconut water, 50% cow urine, and 100 cow urine. At 5 wap, 75% and 100% treatments gave the effect is the same and different from other treatments.